The determinants and value relevance of goodwill impairments in Malaysia firms: The role of corporate governance mechanisms - Al Hiyari, Ahmad Ali Eid (2016)
The purpose of this study is to examine the determinants and the value relevance of goodwill impairments. In contrast to similar studies, this study does not focus solely on management’s opportunistic reporting behavior. Instead, it provides some insights into the likelihood that they exercise their discretion to improve the informational value of accounting information. In addition, this study compares the determinants of goodwill impairments across the pre- and the post Malaysian Code on Corporate Governance 2012 (MCCG 2012) and explores the influence of monitoring mechanisms on shareholders’ valuation assessments of goodwill impairments. By doing so, it extends the literature relating to the role of corporate governance in constraining management’s discretionary behavior associated with goodwill impairment testing. Using panel data over the period 2010 to 2014, the results show that goodwill impairments are associated with “big bath” behavior, an earnings management technique, and CEO changes. The results also indicate that these impairments generate value relevant and bad news to shareholders. Therefore, the combined findings suggest that establishing accounting standards which provide relevant information are difficult to implement reliably. Additionally, this study documents that, except for CEO changes, goodwill impairments have greater association with big bath behavior, and lower association with return on assets subsequent to MCCG 2012 implementation, consistent with criticisms of the MCCG. Finally, this study shows that effective corporate governance mitigates the bad news conveyed by goodwill impairments, indicating that firms with strong monitoring mechanisms are less likely to engage in big bath reporting behavior. Overall, the findings of this study should be useful to standard setters and policy makers who are interested in improving and evaluating the quality of goodwill reporting and corporate governance practices in Malaysia while emphasizing the importance of good corporate governance in ensuring credible accounting information